Pengalaman Suami yang Mengikuti Vasektomi di Kecamatan Cimahi Tengah : Experience of Husbands who Follow Vasectomy in Cimahi Tengah Subdistrict - Fikri Mourly Wahyudi; R. Siti Jundiah; Novitasari Tsamrotul Fuadah; Inggrid Dirgahayu; Yuyun Sarinengsih (NERS Jurnal Keperawatan, 2022)
This research is based on the phenomenon of the low participation of men in family planning, which is only 1,5%, whereas the vasectomy method is only chosen by 0,3% of fertile-age couples. Various reasons make men's participation very low. This research was conducted to explore the experiences of husbands who had gone through vasectomy that could answer the phenomena. The study was conducted on 6 participants married men aged 44 to 62 years old, with the duration of vasectomy in 1 to 25 years. The method used is qualitative research with a phenomenological approach to explore the phenomena that exist in the experience of husbands who had gone through vasectomy procedures. The data of the research was collected through interviews with participants, checked with data triangulation, and analyzed by the Colaizzi approach. The study produced 8 themes: readiness to do vasectomy, pain, anxiety, getting rewards, no physical changes, no changes in sexual intercourse, and rumors, as well as 18 sub-themes. Researchers recommend health education and evaluation of vasectomy acceptors, and further researchers to continue research with other methods so deeper phenomena can be explored.